Deteksi Tepi Sederhana Pada Citra Menggunakan Operator Sobel - Supiyandi Supiyandi; Trisatin Panggabean; Nuzul Ramadhan; Sri Ratna Dewi; Salsabila Yusra (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
implemented and evaluated the edge detection method using the Sobel Operator, which calculates the gradient of image intensity through two convoluted kernels for horizontal (Gx) and vertical directions. (Gy). The magnitudo gradient is obtained from the combination of both such directional gradients to represent the edge force on each pixel. The main steps include image pre-processing, the application of the Sobel kernel, the calculation of magnitudo gradients, and the filtering of results to extract significant edges. The results show that the Sobel Operator is effective in highlighting intensity differences that indicate the boundary of the object, although it is sensitive to noise and less accurate for fine edges. Despite its limitations, this method is simple to implement and useful as an initial step in image processing applications such as segmentation, pattern identification, and object shape analysis.